2012
DOI: 10.1016/j.jhep.2011.05.029
|View full text |Cite
|
Sign up to set email alerts
|

The SOD2 C47T polymorphism influences NAFLD fibrosis severity: Evidence from case-control and intra-familial allele association studies

Abstract: Carriage of the SOD2 C47T polymorphism is associated with more advanced fibrosis in NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
87
2
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(101 citation statements)
references
References 64 publications
(72 reference statements)
0
87
2
7
Order By: Relevance
“…Only a minority of genes associated with NAFLD through candidate-gene analysis have been independently validated in large independent studies or through the use of transmission disequilibrium testing. This short list includes mitochondrial superoxide dismutase 2 (SOD2) 77 , phosphatidylethanolamine Nmethyltransferase (PEMT) 78 , fatty acid desaturase 1 79 and kruppel-like factor-6 (KLF6) 80 . All of these genes were associated with progressive NAFLD rather than NAFLD per se.…”
Section: [H2] Geneticsmentioning
confidence: 99%
“…Only a minority of genes associated with NAFLD through candidate-gene analysis have been independently validated in large independent studies or through the use of transmission disequilibrium testing. This short list includes mitochondrial superoxide dismutase 2 (SOD2) 77 , phosphatidylethanolamine Nmethyltransferase (PEMT) 78 , fatty acid desaturase 1 79 and kruppel-like factor-6 (KLF6) 80 . All of these genes were associated with progressive NAFLD rather than NAFLD per se.…”
Section: [H2] Geneticsmentioning
confidence: 99%
“…SNPs have been found in genes encoding for: the manganese superoxide dismutase (SOD2) regulating mitochondrial import and anti-oxidant activity [18]; the transcription factor Kruppel-like factor 6 (KLF6) regulating metabolism in hepatocytes and fibro genesis in hepatic stellate cells [19]; and the lipin-1 regulating the flux of free fatty acids between the adipose tissue and the liver whose expression is deregulated during steatosis [22]. Finally, there is a growing awareness that phenotypic expression of some genetic variants may be age-related.…”
Section: Nalfd: the Liver At The Centermentioning
confidence: 99%
“…However, the sis have remained undeis have remained unde ide analysis showed th ide analysis showed t ce variation, the ce variation, pata pat containing 3 (PNPLA3 containing 3 (PNPLA3) eotide polymorphism (S otide polymorphism (S ne to methionine varian ne to methionine var erminant of interindiv erminant of interindiv ifferences in hepatic fa fferences in hepatic fa esistance and ser istance and ser also known o know c ret ret nt the results of a met nt the results of a me patients undergoing live tients undergoing live ngth of I148M ngth of I148M PNPLA PNPLA disease severity across d sease severity across d uated, together with ated, together with diate associated p iate associated has definitivel has definitivel impacts no impacts the sus he sus high with other genetic variants influencing the liver fat pathway 15 and fibrosis progression. 3,5,6 More intriguing novel information emerging from the Sookoian and Pirola meta-regression analysis 13 is the negative association between male gender and the effect of the PNPLA3 genotype. In fact, this study has shown that the I148M variant is more effective in increasing the NAFLD risk in females, who are usually protected at the reproductive age.…”
Section: R E T R a C T Ementioning
confidence: 99%
“…1,2 A few large multicenter case-control studies demonstrated a role of genetic variants implicated in insulin signaling, 3 oxidative stress, 4,5 and fibrogenesis 6 in the progression of NAFLD toward fibrosing NASH. However, the inherited determinants of steatosis have remained undetermined until a genomewide analysis showed that a nonsynonymous sequence variation, the patatin-like phosholipase domain-containing 3 (PNPLA3) rs738409 C>G single nucleotide polymorphism (SNP), encoding for an isoleucine to methionine variant (I148M), was a major determinant of interindividual and ancestryrelated differences in hepatic fat content, independently of insulin resistance and serum lipids.…”
mentioning
confidence: 99%